MODEL INSENTIF TAMBAHAN BAGI DOSEN DARI LEBIHAN BKD - Achmad Muhammad; Narwikant Indroasyoko; Nia Nuryanti Permata (Universitas Serambi Mekkah, 2019)
Lecturers in each semester are required to collect “Beban Kerja Dosen (BKD)” and “Evaluasi Kinerja Dosen (EKD)”. Evaluation for “Beban Kerja Dosen” is based on portfolio. Law Number 14 of 2005 requires a “BKD” of at least 12 credits and a maximum of 16 credits. For lecturers whose performance exceeds the required workload must be considered to obtain incentives for the performance achieved. Incentives are direct rewards paid to employees because their performance exceeds specified standards. This study aims to create a model of providing additional incentives for lecturers who perform more according to the results of “BKD” reports of the lecturers. The research method uses descriptive analytic with a qualitative approach. Data collection techniques are observation, interviews, and document study. Additional incentive models from over workload in BKD can be used as an alternative to providing incentives for lecturers with performance that exceeds the requirements.